Engineering the catalyst layers towards enhanced local oxygen transport of Low-Pt proton exchange membrane fuel cells: Materials, designs, and methods. (5th February 2023) - Liu, Shiqing; Yuan, Shu; Liang, Yuwei; Li, Huiyuan; Xu, Zhiling; Xu, Qian; Yin, Jiewei; Shen, Shuiyun; Yan, Xiaohui; Zhang, Junliang
Abstract: Proton exchange membrane fuel cells (PEMFCs) help to achieve decarbonized energy demand due to their advantages of no pollution emission and high power efficiency. But the commercialization of fuel cells has encountered difficulties due to the high-cost issue. The key to addressing the cost issue of PEMFCs lies in reducing Pt amount. However, concentration polarization in the high current density region increases as the decrease of Pt loading, of which the local transport loss of oxygen in the cathode catalyst layer (CCL) occupies the most significant part. Therefore, reducing local oxygen transport resistance is necessary to achieve ultra-low Pt loading in practical PEMFC. This paper focuses on summarizing various electrode design methods for the CCL that optimize the local transport resistance of oxygen, including modifications to the ionomer layer, catalyst structure, and overall electrode structure. Each improvement method is explained with the mechanism of the local oxygen transport process, investigating the effect of different ionomer and Pt-based nanoparticle structures, distribution, and surface chemistries on the local transport pathways. The insights proposed in this paper provide recommendations for the fabrication and design of high-efficiency low-platinum fuel cells. Highlights: Local oxygen transport process and corresponding influence are illustrated. Guidance is provided for the future development of ionomer and catalyst materials. The most recent advances in CL design with low local resistance are summarized.